2020
DOI: 10.5539/ies.v13n5p150
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Webfolios on Saudi EFL Students’ Self-Directed Learning Readiness

Abstract: Webfolios, or web portfolios, are innovative learning tools. Therefore, the objective of this study was to examine the effect of using webfolios on Saudi EFL students’ self-directed learning readiness. Participants were pretested on self-directed learning readiness before starting to work on their webfolios. They used Blackboard to create and use their webfolios. After the webfolios were completed, participants were posttested. A significant effect was found for webfolios on participants’ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…In other words, EPs help students promote their SDEL. This finding is in parallel with several studies [9], [10], and [12] in that the application of EPs developed learners a sense of ownership and encouraged their independence in learning. In addition, they were able to manage their personal learning progress through the use of EPs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In other words, EPs help students promote their SDEL. This finding is in parallel with several studies [9], [10], and [12] in that the application of EPs developed learners a sense of ownership and encouraged their independence in learning. In addition, they were able to manage their personal learning progress through the use of EPs.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this research revealed that EPs have provided the participants with a lot of benefits and the most significant one was the development and encouragement of independent learning [9]. Another research considering the effectiveness of webfolios on Saudi EFL students' readiness for SDL was [10], and it was concluded that adopting webfolios promoted the SDL readiness of Saudi EFL students. Therefore, it is highly recommended that web-based programs should be employed in order to teach English as a foreign language.…”
Section: Introductionmentioning
confidence: 86%
“…Justus et al, (2022) argue that self-directed learning is a process that makes students responsible for planning, undertaking, and reviewing aspects of their learning process. It has also been advanced by (Zakareya & Al-Qahtani, 2020) who call this transition the biggest undertaking of the twenty-first century. Liu et al, (2020) stressed that this new pedagogical approach inspires students to engage in self-directed learning (SDL) through online learning.…”
Section: Self-directed Learning In Listening Skillmentioning
confidence: 99%
“…Besides that, the teacher knows that self-directed learning can improve students' responsibility and give them the independence to learn. In doing the online learning process, the teacher knows that they can learn anytime and everywhere that is supported by using information and communication technologies within the line of the study from Zakareya and Al-Qahtani (2020). Those perceptions of content knowledge have the same purpose with the learning autonomy which is to give the independent learning in managing their own learning based on Holec's perspective (1981) as cited in Bravo et al, (2017), self-directed learning make the teacher ready in doing selfdirected learning.…”
Section: Influentialmentioning
confidence: 99%